Infection and risk perception of sars-cov-2 among airport workers: A mixed methods study (2020)
This is a mixed-methods research study carried out on a cohort of airport workers during the SARS-CoV-2 pandemic. We used quantitative and qualitative methods to describe the infection and risk perception of SARS-CoV-2 in a cohort of workers at the International Airport El Dorado/Luis Carlos Galán Sarmiento in Bogotá, Colombia. An incidence of SARS-CoV-2 infection of 7.9% was found in the workers. A high perception of risk was associated with activities such as using public transport. Risk perception is strongly influenced by practices related to work conditions and environments. These findings could help us understand the pandemic’s dynamics and the conceptions of the risk of transmission to promote policies on health and safety in this group of workers.